Forecasting Straight Line Methodin The Les Monitoring System Read The Great Children (AHE) in Kudus - Aprilia Shanti Setyorini; Tri Listyorini; Endang Supriyati (JURNAL TEKNIK INFORMATIKA, 2022)
The existence of the Covid-19 virus has an impact on almost all fields, one of which is in the field of education. With the Covid-19 virus, the learning process has changed to distance learning or online. Online learning requires parents to be able to accompany their children in learning. However, not all parents can accompany their children to study because of their busy schedule at work, or the parents' low level of education. Therefore, the existence of tutoring or tutoring places is sought to assist parents in educating their children in the midst of a pandemic. Les Baca Anak Hebat (AHE) is a special community tutoring for reading and writing. Its development in Indonesia is increasing from village to village. In Kudus City itself there are many villages that have units. With this significant number of students, the number of existing students also affects the continuation of the unit. To avoid a spike in the number of students, we need a system that can monitor or predict the number of students in the future so that no units are closed. To estimate the number of students can use one of the fields of science such as forecasting. One of the forecasting methods is the Straight Line Method. In developing the system the author uses the waterfall method with the PHP programming language and MySQL database. This web-based system is used to monitor AHE units in Kudus.